The Learning of Narrative Writing Skills through Experiential Learning Model in Elementary School Students - Ahwi, Rahmania Savitri; Iswara, Prana Dwija; Tursiva, Erva (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
This research was motivated by the low skills of writing narrative text in the fifth-grade elementary school students. Students have difficulty getting ideas in putting them into narrative text. The experiential learning model was chosen because it can make the students easier to find ideas in writing a narrative text. The purpose of this study was to describe the learning process by using the experiential learning model to improve students' narrative writing skills. This research is a qualitative study and using descriptive methods. The instrument data used was a written test of writing narrative text. Participants in this study were 31 students of V-B class at SDN Bedahan 01 Cibinong, Bogor. The results showed that the learning process using an experiential learning model consisting of concrete experience steps, reflective observation, abstract conceptualization, and active experimentation can improve students' narrative writing skills. The pre-test average score written by the student's narrative was 53 while the post-test average score of the students was 80. This research concluded that the learning process through the experiential learning model can improve the narrative writing skills of fifth-grade elementary school students.